Motor Vehicle Behavior Analysis of Side Obstacles - Suprapto Hadi; Yogi Oktopianto; Siti Shofiah; I Made Sukmayasa (Pusat Penelitian dan Pengabdian Masyarakat Poltrada Bali, 2022)
High side barriers cause road sections to experience traffic jams. On the Pantura road, Brebes Regency, many vehicles tend to stop or reduce their speed due to many side obstacles that interfere with the journey, including tricycles, parking vehicles and so on. This study aims to analyze the behavior of motorists on each type of motorized vehicle against side obstacles. The research method is carried out directly by observers and is qualitative in nature based on normative standards in the 1997 MKJI. The results of the research show that the driver's behavior is influenced by side barriers, in this case the vehicle speed that the larger the side obstacle class, the lower the vehicle speed. On roads with a higher left lane speed than the right lane, on that road heavy vehicles tend to choose the right lane, this condition is because heavy vehicles avoid side obstacles in the left lane and on the left lane more light vehicles pass. On the other hand, on roads with a higher right-hand lane speed than the left lane, heavy vehicles that pass tend to choose the left lane for this condition because the side barriers in the left lane do not have a major effect on traffic on that lane.